Digital Transformation of Islamic Boarding Schools: Developing Smart Pesantren through Educational Technology Integration - Mowafg Masuwd; Markhabat Bolat; Mohammad Ahmad Bani Amer (PT Barkah Ilmi Fiddunya, 2025)
Islamic boarding schools (Pesantren) are experiencing increasing pressure to adapt to digital transformation while preserving their traditional educational identity. This study aims to analyze strategies for developing Smart Pesantren through the integration of educational technology, digital management systems, and Islamic values. A multiple-case qualitative study was conducted across several modern Islamic boarding schools implementing digital innovation. Data were collected through interviews with school leaders, teachers, students, classroom observations, and institutional documentation. The findings reveal that successful digital transformation depends on visionary leadership, digital infrastructure, teacher competence, curriculum innovation, and institutional culture. Technology integration enhances administrative efficiency, instructional quality, student engagement, and access to digital Islamic resources while maintaining the spiritual traditions of pesantren education. The study also identifies several implementation challenges, including digital literacy gaps, infrastructure disparities, and resistance to organizational change. The novelty of this research lies in developing the Smart Pesantren Transformation Framework, which integrates educational technology, Islamic leadership, institutional governance, and pesantren values into a comprehensive digital transformation model